Percutaneus Mitral Valvuloplasty in Adult Patients with Rheumatic Mitral Stenosis - Results of 200 Cases - Anam, Md Khairul; Rahman, Fazlur; Hussain, Khondoker Shahid; Uddin, Mir Jamal; Ahmed, Chaudhury Meshat; Ahmed, Md Khurshed; Banerjee, Sajal Krishna; Siddique, Md Abu; Hasan, ATM Iqbal (University Heart Journal, 2011)
This prospective study was carried out in the department of cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka and National Institute of Cardiovascular Disease (NICVD), Dhaka between July 2006 to July 2010. Total 200 patients underwent percutaneous mitral commissurotomy. Mitral valve dilatation resulted in increase in mitral valve area from .6±0.26 to 1.70±.38cm2 (p<0.001). Mitral valve mean pressure gradient declined from 23.00±5.38 to 6.8±2.98mmHg (p<0.001). The pulmonary artery systolic pressure decreased from 73.8±19.30 to 29.26±11.80mmHg (p<0.001). Procedural success, as defined as final mitral valve area >1.5cm2 or >50% increase in area, was achieved in 95% patients. Serious complications occured in 10 patients Death occurred in two patient (1%). Minor complication such as vasovagal reaction (5%), balloon rupture without sequel (0.5%), pericardiocentesis (.5%), mitral regurgitation (3%), hypotension (1%), seizure (2%), drug reaction (1%) were also noted. The adverse hemodynamic effect of mitral stenosis may be relieved by percutaneous transvenous mitral commissurotomy but it is not without risk. The morbidity & mortality is very low in properly selected patient. This study demonstrate excellent short term clinical & hamodynamic outcome of this procedure and very low procedure related complications. Key words: Mitral Stenosis; Balloon Valvuloplasty DOI: 10.3329/uhj.v6i2.7246 University Heart Journal Vol. 6, No. 2, July 2010 pp.65-69